Plane-strain consolidation theory with distributed drainage boundary - Chen, Z. (2021)
In practice, the full arrangement of sand blankets overlying soft clays could result in an uneconomic design for soft soil treatment using the surcharge preloading method. In view of this, a novel type of distributed drainage boundary is proposed in this investigation to improve the design. A two-dimensional plane-strain consolidation problem with distributed drainage boundary is established and solved. The sensitivity of the consolidation process to the pave rate (sand blanket area over the total area), thickness–width ratio (thickness over width of the representative element) and anisotropy coefficient (horizontal consolidation coefficient over vertical consolidation coefficient) are discussed. The results show that the negative effects of distributed drainage on the consolidation process become negligible if the pave rate and thickness–width ratio are designed adequately. Remarkably, the distributed drainage boundary becomes more efficient with the decrease in anisotropy coefficient. In addition, the increasing rate of consolidation time calculated using different parameters is presented for four average degrees of consolidation to provide a theoretical reference for engineering design.